Paradigm Transformation of Mental Health Services through Complementary and Alternative Medicine (CAM) by Psychology Students in Health Education Institutions - Khaira, Himmatul; Sihombing, Roy Wilson Putra (Journal of Health Innovation and Environmental Education, 2025)
Purpose of the study: This study aimed to explore the lived experiences of psychology students in implementing Complementary and Alternative Medicine (CAM) and to analyze how such experiences contribute to the transformation of mental health service paradigms toward a holistic and integrative model.Methodology: A qualitative study with a phenomenological approach was conducted among psychology students at UIN Syarif Hidayatullah Jakarta. Participants were selected through purposive sampling. Data were collected using in-depth semi-structured interviews and analyzed following Colaizzi’s phenomenological method, including significant statement extraction, meaning formulation, theme clustering, and validation through member checking.Main Findings: Six major themes emerged: (1) holistic meaning construction of CAM, (2) technical and procedural experience, (3) perceived psychological and physiological benefits, (4) complementary versus substitutive positioning, (5) ethical awareness and patient safety, and (6) professional identity transformation. Participants predominantly positioned CAM as a complementary intervention that enhances emotional regulation, therapeutic readiness, and culturally sensitive care. The findings indicate a paradigm shift from a biomedical orientation toward a biopsychosocial-spiritual mental health framework.Novelty/Originality of this study: This study contributes a novel perspective by positioning CAM not solely as a therapeutic modality but as an educational catalyst for transforming professional identity and mental health service paradigms within psychology training.